Complying with Act 141: Renewable Electricity Consumption at State Facilities - Sayen, Nicholas; Matz, Hy; Johnson, Erik; Blonn, Jennifer (My University, 2007)
Act 141 specifically calls for the Wisconsin's government to acquire 10 percent of its electricity from renewable resources by December 31, 2007, and 20 percent by December 31, 2011. This report advises the Wisconsin Department of Administration in complying with these targets. The authors recommend that the Department of Administration purchase renewable electricity from local utilities that have invested in in-state state resources to meet Act 141's target.